A Test Development Study on Spatial Visualization for Second-Grade Primary School Students - Demirel, Sevgi; Cetin, Hatice (International Electronic Journal of Elementary Education, 2023)
This study aims to develop a new spatial visualization test (SVT) for second grade primary school students. The study employed the survey design, and the test was developed in accordance with the test development steps. According to the findings obtained as a result of the pilot study, the items were generally high difficulty levels, and they were very good items. Exploratory and confirmatory factor analysis findings confirmed the three sub-dimensions (mental integration, mental rotation and paper folding) measuring spatial visualization skills. SVT, which was reduced to 10 items, was administered to 396 students; the KR-20 internal consistency coefficient was 0.63, the average difficulty index was 0.35 and the average discrimination index was 0.48. As a result of the study, a valid and reliable test on spatial visualization for second grade primary school students was obtained and it was concluded that students' spatial visualization was at a low level